Thermoplasmonic Response of Semiconductor Nanoparticles: A Comparison with Metals. Issue 1 (22nd October 2018) - Thakore, Vaibhav; Tang, Janika; Conley, Kevin; Ala‐Nissila, Tapio; Karttunen, Mikko
Abstract: A number of applications in nanoplasmonics utilize noble metals, gold (Au) and silver (Ag), as the materials of choice. However, these materials suffer from problems of poor thermal and chemical stability with significant dissipative losses under high‐temperature conditions. In this regard, semiconductor nanoparticles have attracted attention with their promising characteristics of highly tunable plasmonic resonances, low ohmic losses, and greater thermochemical stability. Here, the size‐dependent thermoplasmonic properties of semiconducting silicon and gallium arsenide nanoparticles are investigated to compare them with Au nanoparticles using Mie theory. To this end, experimentally estimated models of dielectric permittivity are employed. Among the various permittivity models for Au, the Drude–Lorentz (DL) and the Drude and critical points (DCP) models are further compared. Results show a redshift in the scattering and absorption resonances for the DL model while the DCP model presents a blueshift. A massive Drude broadening contributes strongly to the damping of resonances in Au nanoparticles at elevated temperatures. In contrast, the semiconductor nanoparticles do not exhibit significant deterioration in their scattering and absorption resonances at high temperatures. In combination with low dissipative damping, this makes the semiconductor nanoparticles better suited for high‐temperature applications in nanoplasmonics wherein the noble metals suffer from excessive heating. Abstract : The thermoplasmonic responses of indirect (silicon) and direct (gallium‐arsenide) bandgap semiconductor nanoparticles are compared with the metallic (gold) nanoparticles using Mie theory in conjunction with experimentally estimated models of dielectric permittivity. High values of quality factors for the resonances in silicon nanoparticles and the spectral selectivity of the absorption efficiency in gallium‐arsenide nanoparticles are maintained at elevated temperatures in contrast to the gold nanoparticles.